Pengembangan E-Modul Berbasis Pendekatan Problem Based Learning Untuk Meningkatkan Pemahaman Siswa Pada Pembelajaran Tematik Kelas V Tema 9 Subtema 3 SDN 107418 Bangun Sari Baru T.A 2022/2023 - Herzegovina, Lusitania; Perangin-Angin, Laurensia M.; Simbolon, Naeklan; Sitohang, Risma; Mailani, Elvi (Journal of Student Development Information System (JoSDIS), 2023)
This study aims to determine the validity of the feasibility, practicality and effectiveness of using Problem Based Learning (PBL) E-Modules in thematic learning class V Theme 9 Sub-theme 3 SDN 107418 Bangun Sari Baru. The method used in this study is R&D (Research and Development) using the ADDIE development model which consists of 5 stages namely Analysis, Design, Development, Implementation, Evaluation. In this study the product developed was the E-Module based on Problem Based Learning (PBL). The subjects in this study were clear V students at SDN 107418 Bangun Sari Baru, totaling 22 students. The objects in this study consisted of material experts, design experts and class teachers. The instruments used in this study were interviews, questionnaires and tests. The test questions used are pre-test and post-test. The results of the pre-test get an average score of 66.27 with the criterion "Not Enough" and the post-test score gets an average score of 87 "Very Good" from these results there is an increase. Through the acquisition of post-test scores, all students pass the minimum completeness criteria (KKM). The results showed that the average percentage obtained from the validation of Â¬E-Module design experts was 96% with a "Very Eligible" percentage, Material expert validation was 91% with a "Very Eligible" percentage. The practicality test results by educational practitioners obtained a result of 96% "very good" with the completeness criterion "Completed". Thus it can be concluded that the Problem Based Learning-based E-Module in thematic learning of class V Theme 9 Sub-theme 3 can be used in the learning process in elementary school.